The role of the immunological background of mice in the genetic variability of Schistosoma mansoni as detected by random amplification of polymorphic DNA. Issue 6 (November 2015) - Cossa-Moiane, I.L.; Mendes, T.; Ferreira, T.M.; Mauricio, I.; Calado, M.; Afonso, A.; Belo, S.
Abstract Schistosomiasis is a parasitic disease caused by flatworms of the genus Schistosoma. Among the Schistosoma species known to infect humans, S. mansoni is the most frequent cause of intestinal schistosomiasis in sub-Saharan Africa and South America: the World Health Organization estimates that about 200, 000 deaths per year result from schistosomiasis in sub-Saharan Africa alone. The Schistosoma life cycle requires two different hosts: a snail as intermediate host and a mammal as definitive host. People become infected when they come into contact with water contaminated with free-living larvae (e.g. when swimming, fishing, washing). Although S. mansoni has mechanisms for escaping the host immune system, only a minority of infecting larvae develop into adults, suggesting that strain selection occurs at the host level. To test this hypothesis, we compared the Belo Horizonte (BH) strain of S. mansoni recovered from definitive hosts with different immunological backgrounds using random amplification of polymorphic DNA–polymerase chain reaction (RAPD-PCR). Schistosoma mansoni DNA profiles of worms obtained from wild-type (CD1 and C57BL/6J) and mutant (Jα18− / − and TGFβRIIdn) mice were analysed. Four primers produced polymorphic profiles, which can therefore potentially be used as reference biomarkers. All male worms were genetically distinct from females isolated from the same host, with female worms showing more specific fragments than males. Of the four host-derived schistosome populations, female and male adults recovered from TGFβRIIdn mice showed RAPD-PCR profiles that were most similar to each other. Altogether, these data indicate that host immunological backgrounds can influence the genetic diversity of parasite populations.